An adaptive audio watermarking system - Foo, Say Wei (2009)
An adaptive and content-based audio watermarking system based on echo hiding is presented. The proposed system aims to overcome the problems of audible echoes in a simple echo hiding approach. Audibility of echoes is reduced especially for problematic signals by the application of signal-based attenuation, psycho-acoustic model and perceptual filter to adaptively modify the decay rate used in encoding the watermark. The proposed method is robust to common signal processing operations of noise addition, re-sampling, cropping, filtering and MPEG coding. If inaudibility and detection accuracy are of paramount importance, a psychoacoustic model coupled with single echo is the most appropriate encoding option to use when additional signal processing is imposed. The application of multiple echo hiding is also investigated. It is found that although multiple echo hiding improves inaudibility in general, detection accuracy is compromised when additional signal processing is imposed